ANALISIS KUANTITATIF CEMARAN LOGAM BERAT PADA MINUMAN SERBUK TRADISIONAL BERBASIS KUNYIT (Curcuma longa L) - Chairunisa Ayu Saputri; Emi Novita Sari (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Traditional herbal drinks have many health benefits because they contain active ingredients. Traditional drinks that are widely marketed are liquids that cannot be stored for long periods. One way to extend the shelf life is by formulating it into powder. Powdered drinks are more practical and easier to serve so it is hoped that they will be well received by consumers. Heavy metal contamination is an indicator that needs to be considered in food safety. The presence of heavy metal contamination in this study, namely Pb and Cu, can occur during the processing of traditional drinks or in the raw materials used. In this research, 3 turmeric-based powder drink formulations (Curcuma longa L) were carried out, with several other ingredients, namely tamarind, cinnamon, lemongrass and cloves with variations in the amount of sugar added. Analysis of heavy metal contamination was carried out on fresh turmeric raw materials and on powdered drink products. The test results show that in fresh turmeric raw materials there is 0.423 mg/kg Cu and 0.012 mg/kg lead. Tests on the three turmeric powder drink formulations, namely F1: contained 0.595 mg/kg Cu and 0.018 mg/kg lead. In F2 there was 0.435 mg/kg Cu and 0.005 mg/kg lead. In F3 there was 0.672 mg/kg Cu and 0.008 mg/kg lead. These results still meet the quality requirements for traditional powdered drinks based on SNI 01-4320-1996.